Study of the exotic structure of neutron-rich 14B and 17C nuclei using the binary cluster model - F. Sultan, Luay; N. Abdullah, Ahmed (Al-Nahrain Journal of Science, 2020)
The neutron, proton, and matter densities of the ground state of the 14B and 17C exotic nuclei are analyzed using the binary cluster model (BCM). Two density parameterizations are used in BCM calculations namely; Gaussian (GS) and harmonic oscillator (HO) parameterizations. According to the calculated results it found that, the BCM gives a good description of the nuclear structure for above neutron-rich exotic nuclei. The elastic form factors of the unstable 14B and 17C exotic nuclei and those of their stable isotopes 10B and 13C are determined using the plane-wave Born approximation. The main difference between the elastic form factors of unstable nuclei and their stable isotopes is due to the difference in the center of mass correction. Moreover, the Glauber model is used to calculated the matter rms radii and reaction cross section of these exotic nuclei.  The calculate results of the mentioned nuclei give a good accordance with the experimental data.